Keragaman Morfologi dalam Galur dan Hubungan Kekerabatan Enam Galur Kacang Bambara (Vigna subterranea (L.) Verdcourt) sebagai Dasar Seleksi Tetua Pemuliaan - Ahmad Alif Riyan Mahdy; Rima Rahma; Sitaningrum Hayatunnufus; Kuswanto (AGROISTA : Jurnal Agroteknologi, 2026)
Bambara groundnut (Vigna subterranea L. Verdc.) is a drought-tolerant legume with high nutritional value, yet its development in Indonesia remains constrained by low productivity and seed heterogeneity due to the absence of established national varieties. This study aimed to evaluate morphological variability within lines and determine the phylogenetic relationships among six bambara groundnut lines: SS 3.4.2, SS 2.4.2, PWBG 6, BBL 1.1, CCC 1.6, and TVSU 86. Morphological characterization was conducted based on IPGRI descriptors, covering 15 quantitative and 8 qualitative traits. Intra-line variability was assessed using the coefficient of variation (CV), while phylogenetic relationships were analyzed through UPGMA cluster analysis with Simple Matching Coefficient using MVSP 3.2 software, performed separately for qualitative traits and for combined quantitative–qualitative traits. Results showed that yield-related characters such as pod length, pod width, seed length, and seed width exhibited very high CV values across all lines, indicating the need for further intensive selection to achieve phenotypic stability. Qualitative analysis produced similarity values of 85%–100%, while the combined analysis yielded 50%–88%, demonstrating greater discriminating power among lines. Based on component yield performance, the SS 3.4.2 line excelled in pod length, pod width, and seed width; the SS 2.4.2 line excelled in seed length and seed width; while the PWBG 6 line excelled in pod length and possessed the farthest genetic distance. Lines from these different clusters are recommended as crossing parent combinations: SS 3.4.2 × SS 2.4.2; SS 2.4.2 × PWBG 6; as well as their reciprocals, for yield component improvement and broader genetic variability. These findings confirm the utility of morphological characterization as a foundational approach for parental selection in bambara groundnut breeding programs.